(untitled) (Journal of Pharmaceutical Negative Results, 2023)
Background: Psoriasis is a common chronic, disfiguring, inflammatory skin condition in which both genetic and environmental influences play a critical role. It is clinically characterised by sharply demarcated, erythematous, silvery-white, scaly, indurated plaques mainly distributed over extensor surfaces, the lower back, and the scalp. The present study compared acitretin and methotrexate in patients with psoriasis. Aims and objectives: The present study compared acitretin and methotrexate in patients with psoriasis. Materials & Methods: 100 patients with palmoplantar psoriasis of both genders were divided into 2 groups. Each group consisted of 50 patients. Group I patients were given oral acitretin 0.5 mg/kg daily for 3 months, and patients in group II were given oral methotrexate 15 mg/week for 3 months. A modified psoriasis area severity index (MPASI) score was recorded in both groups. Results: Group I had 25 males and 25 females, and Group II had 22 males and 28 females. The mean MASI score at baseline, 1 month, 2 months, and 3 months was 61.4, 41.6, 33.4, and 21.8 in group I, respectively. The mean MASI score in group II was 57.8, 37.4, 24.6, and 15.4 at baseline, 1 month, 2 months, and 3 months, respectively. The difference was significant (P <0.05). Efficiency was excellent in 95 in group I and 97 in group II, good in 5 in group I and 3 in group II, and fair in 1 in group II. The difference was non- significant (P> 0.05). Conclusion: Acitretin and oral methotrexate were found to be efficient in treating palmoplantar psoriasis. The efficacy of both drugs was found to be comparable.